Enhancing digital transformation capacity of educators to optimize school governance - Tirta Anhari; Ahmad Said (HAMKA INSIGHT, 2026)
Purpose: This study evaluates the effectiveness of implementing an information technology paradigm at SMK Muhammadiyah Al Kautsar Jakarta to resolve critical operational bottlenecks. Specifically, it addresses systemic infrastructure inequality, low digital literacy among educators, organizational resistance, and weak digital service governance that hinder academic management. Method: Adopting a qualitative case study design, data were collected from key school stakeholders through in-depth interviews, direct operational observations, and document analysis of curriculum and digital policy records. The gathered empirical data were analyzed using an interactive model comprising data reduction, data presentation, and conclusion drawing. Findings: Targeted training significantly enhanced stakeholders' comprehension, shifting their perception of technology from a costly administrative burden to a core strategic asset. By holistically addressing sociological and governance root causes alongside technical skills, the intervention strengthened data security awareness, educational service quality, and data-driven decision-making. However, achieving complete organizational transformation requires long-term funding and continuous monitoring. Practical implications: Provides vocational education practitioners and administrators with actionable strategies to integrate technical upskilling with adaptive governance frameworks, thereby optimizing operational efficiency. Originality/value: Offers a novel comprehensive framework that integrates sociological and governance dimensions to overcome technology adoption barriers in Indonesian vocational high schools.